A multilevel analysis of climate change inaction: case study of an Australian electricity company. Issue 2 (2nd April 2020) - Mishra, Kirti; Neesham, Cristina; Coghill, Ken; Stubbs, Wendy
ABSTRACT: Climate change is a key societal and economic challenge. Despite widespread recognition for the need for urgent action on climate change, transformation to a zero carbon economy is still elusive. While there are detailed accounts of organisational responses to climate change impacts, little is known about climate change inaction . We adopt the theoretical framework of resilience in social-ecological systems to explore the change processes needed to overcome climate change inaction. Through an in-depth case study of an Australian energy company, we identify the impediments to climate change action due to rigidity and scarcity traps at three levels: micro (organisation), meso (industry), and macro (government). These traps inhibit transformation from a fossil fuel regime to a renewable energy regime. Our study contributes to a multi-level theory of organisational inaction on climate change by identifying specific causal factors that erode systemic adaptive capacity, increasing the probability of rigidity and scarcity traps. We find that different inaction occurs at all three levels, and is closely interconnected (across levels) within a social-ecological system, due to dynamic antecedents (e.g. changing individual attitudes, business practices, and government policies). Competencies, resources, and cultural changes can help organisations traverse rigidity and scarcity traps to overcome climate change inaction.